2014
DOI: 10.1089/scd.2013.0373
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Regulation of Telomerase Isoforms in Human Embryonic Stem Cells

Abstract: Recent evidence points to extra-telomeric, noncanonical roles for telomerase in regulating stem cell function. In this study, human embryonic stem cells (hESCs) were cultured in 20% or 2% O 2 microenvironments for up to 5 days and evaluated for telomerase reverse transcriptase (TERT) expression and telomerase activity. Results showed increased cell survival and maintenance of the undifferentiated state with elevated levels of nuclear TERT in 2% O 2 -cultured hESCs despite no significant difference in telomeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 106 publications
2
29
0
Order By: Relevance
“…Splicing role of HIF-1 and hypoxia on hTERT. hypoxia is known to enhance hTERT expression through activation of the hTERT promoter in stem cells as well as in cancer (50,51). In hypoxic tumor conditions, hIF-1 is overexpressed and activates the hTERT promoter by binding at two sites between -165 and +51.…”
Section: Role Of Transcription Factor Binding On Splicingmentioning
confidence: 99%
“…Splicing role of HIF-1 and hypoxia on hTERT. hypoxia is known to enhance hTERT expression through activation of the hTERT promoter in stem cells as well as in cancer (50,51). In hypoxic tumor conditions, hIF-1 is overexpressed and activates the hTERT promoter by binding at two sites between -165 and +51.…”
Section: Role Of Transcription Factor Binding On Splicingmentioning
confidence: 99%
“…Correlations of expression levels of alternatively spliced hTERT mRNAs relative to full‐length hTERT mRNA with cell proliferation, cell differentiation and cancer subtype have also been reported (Ulaner et al., ; Brenner et al., ; Fajkus et al., ; Hisatomi et al., ; Petrenko et al., ; Listerman et al., ). Relative levels of specific hTERT isoforms are also important for human embryonic stem (ES) cell self‐renewal and differentiation, with specific isoforms possibly enriching differentiation towards specific cell lineages (Radan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In partial agreement, chemical inhibition of hTERT activity in hESCs leads to lowered pluripotency and increased differentiation, while curiously, similar blocking of telomerase activity through TERC steric inhibition has no effect suggesting an extra-telomeric role for TERT in maintaining self-renewal in the undifferentiated state. 85 In contrast, Sexton et al did not observe any reduction in pluripotency (as measured by sustained OCT3/4 expression only) after establishing stable hESC lines through zinc finger-mediated knockout of hTERT. 86 However, Sexton et al do observe a loss of selfrenewal and differentiation beginning around 75 days post TERT-knockout, when the cells reach a critical telomere length of 2-3kb.…”
Section: Pluripotency and Canonical Tert Functionsmentioning
confidence: 92%
“…138 However, Listerman et al and our group have recently shown that the b-variant transcript associates with polyribosomes, escapes NMD, and is likely translated. 24,85 Surprisingly, the b-deletion transcript not only survives degradation but is one of the most highly expressed TERT transcripts in various cell types including human embryonic stem cells. 24,128,132,147,151 A recent discovery suggests that the b-variant inhibits telomerase activity by sequestering TERC.…”
Section: 135mentioning
confidence: 99%